Ensuring the Right of a Person Suspected of Committing a Crime to Know the Materials of the Criminal Case (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article is aimed at protecting the rights and legitimate interests of a suspect in the course of criminal proceedings, during which it is his right to protection that has been investigated. Awareness of persons defending their interests in criminal proceedings, based on the materials of work at the early stages of the process, affects the effective organization of protection. The subject, who is obliged to prove, will have to provide the suspect with sufficient time and conditions to organize his defense. The article uses a comparative analysis to study the current state of our national criminal procedure legislation on the relevant issue, the experience of developed foreign countries.